2011
DOI: 10.1089/ees.2010.0227
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Sucralose During Wastewater Treatment

Abstract: Sucralose, a chlorinated carbohydrate, is used as an artificial sweetener in more than 80 countries and in excess of 4,000 products. Thus far, minimal research has been done on the degradation and fate of sucralose in municipal wastewater treatment plants (WWTPs). We collected samples from WWTPs and surface waters in Arizona, United States. The average sucralose concentration of seven WWTP effluents was 2,800 ± 1,000 ng/L. Similarly, surface waters in Arizona contained sucralose at concentrations up to 300 ± 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 32 publications
5
56
0
Order By: Relevance
“…The high sucralose concentrations come from the diet of the people in the south of China, who prefer sweetened food. The persistence of sucralose in wastewater treatment plants (WWTPs) and the aquatic environment (Mead et al, 2009;Torres et al, 2011) was another reason for the high sucralose in the river. The load of sucralose in the Yangtze River amounted to 169 t/yr, representing 85% of the sucralose consumption in China (200 t/yr).…”
Section: Household Chemicals and Pharmaceuticalsmentioning
confidence: 99%
“…The high sucralose concentrations come from the diet of the people in the south of China, who prefer sweetened food. The persistence of sucralose in wastewater treatment plants (WWTPs) and the aquatic environment (Mead et al, 2009;Torres et al, 2011) was another reason for the high sucralose in the river. The load of sucralose in the Yangtze River amounted to 169 t/yr, representing 85% of the sucralose consumption in China (200 t/yr).…”
Section: Household Chemicals and Pharmaceuticalsmentioning
confidence: 99%
“…Therefore, in addition to degradation assays, bioassayscould be conducted to evaluate its toxicity. Studies with aerobic and anaerobic biological reactors have shown that these processes were not able to degrade the molecule [15].…”
Section: Introductionmentioning
confidence: 99%
“…The chlorinated structure of the sucralose seems to be resistant to microbial degradation even in the mixed media of a sewage treatment facility, which explains its persistence through wastewater treatment processes in municipal plants (Soh et al, 2011a;Torres et al, 2011) and likely resulting in the high concentrations observed in reclaimed water. Sucralose has become the most detected unregulated chemical and artificial sweetener in wastewater, surface water and groundwater samples (Lange et al, 2012a).…”
Section: Applicability Of the Methods To Environmental Samplesmentioning
confidence: 99%
“…Antibiotics can be classified on the basis of their structure, mode of action or spectrum of activity. Different classes of antibiotics include sulfonamides, quinolones, tetracyclines, macrolides, beta lactams and other miscellaneous ones (Moore, 2013 artificial sweetener in over 4,000 consumer products all over the world (Torres et al, 2011). The most familiar consumer product of sucralose is Splenda, which contains 1% sucralose and 99% maltodextrin and dextrose.…”
Section: Target Cecsmentioning
confidence: 99%
See 1 more Smart Citation